Risk Analysis by Fine Kinney Method in a Laboratory - Yalçın, Zehra Gülten; Dağ, Mustafa; Aydoğmuş, Ercan (Niyazi BULUT, 2018)
In this study, a risk assessment was performed by Fine-Kinney method in various units of an official institutional laboratory. For this purpose, feasibility of the laboratory determinated, devices and areas with high risk priority were identified. In hazardous areas, High-risk materials such as store chemical material, spare part production, molding and pressing, rubber production and shredding, plastic breaking, deburring, cutting and packaging, plastic injection molding machines used. The risks identified in these units can be stated as follows; injury by exposure to chemical materials, diarthrosis and spinal cord injury, limb loss, hearing loss, etc. In these units, the risk assessment was carried out by the Fine Kinney method and necessary precautions were taken and necessary arrangements were made. These measures are applying the control protocol for routine execution of the process, training of personnel for each unit according to ISG rules and giving training seminars at regular intervals, protective clothing and equipment used during operation, regular maintenance and repairs of units. After these precautions, "risk acceptable" values are obtained by carrying out risk preventive activities in regions with the highest risk.